▼Pregabalin for generalised anxiety disorder. Issue 2 (10th February 2010) - Unknown
Abstract : Generalised anxiety disorder (GAD) is common, with a prevalence of around 4% among adults in the UK.1 The condition is characterised by chronic excessive anxiety and worry, in combination with a variety of psychological or somatic symptoms. It can be very distressing and disabling and, if left untreated, can be costly to both the individual and society.2 ▼Pregabalin (Lyrica – Pfizer) is a medicine licensed for GAD in adults.3 Here we review its role in the management of patients with the problem.